Under Reporting of Suicide Ideation in US Army Population Screening: An Ongoing Challenge. Issue 6 (15th December 2016) - Vannoy, Steven D.; Andrews, Bonnie K.; Atkins, David C.; Dondanville, Katherine A.; Young‐McCaughan, Stacey; Peterson, Alan L.; ,
Abstract : Previous research in US Army Soldiers shows rates of mental health concerns as two to four times higher on anonymous surveys than on postdeployment health assessments. In this study, Soldiers presenting for health reassessment completed two questionnaires on suicide risk factors: one linked to the health assessment and one anonymous. About 5.1% of respondents reported suicide ideation on the anonymous questionnaire, 3.0% on the linked questionnaire, and 0.9% on the health reassessment. About 56.4% who reported suicide ideation anonymously told nobody of their thoughts. Current screening procedures identify only one in seven Soldiers experiencing suicide ideation and highlight the need for alternative risk‐detection strategies.